2017
DOI: 10.1051/kmae/2017047
|View full text |Cite
|
Sign up to set email alerts
|

Management of pikeperch stocking in Lake Balaton: effect of season, area, fish size and method of release on the rate and distribution of recaptures

Abstract: -Pikeperch Sander lucioperca is an economically important fish which depleted populations need intensive management and supplemental stocking. We aimed to assess the relative influence of various pikeperch stocking strategies in Lake Balaton, Hungary, and tested 60 stocking set-ups (two seasons  three lake areas  shore vs. offshore release  five size groups) by releasing 3000 tagged yearlings. Anglers reported data of 522 recaptures within four years after stocking. Recapture rate was highest in stocking of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
(58 reference statements)
2
9
0
Order By: Relevance
“…In spite of its higher diversity, the wild population showed the signs of a recent bottleneck event. Specziár & Turcsányi (2017) reported that the pikeperch population of Lake Balaton is characterized by a high rate of harvesting, an early-life dietary bottleneck and a high rate of predation and cannibalism-related juvenile mortality. All of these factors can greatly reduce population size, resulting in changes in the genetic structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of its higher diversity, the wild population showed the signs of a recent bottleneck event. Specziár & Turcsányi (2017) reported that the pikeperch population of Lake Balaton is characterized by a high rate of harvesting, an early-life dietary bottleneck and a high rate of predation and cannibalism-related juvenile mortality. All of these factors can greatly reduce population size, resulting in changes in the genetic structure.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of β increases as the proportion of reproductive captive individuals within the stock increases. Specziár & Turcsányi (2017) reported on the annual stocking of 1-1.5 million fingerlings into Lake Balaton. Based on mark-recapture data, they found an average 7.7% survival at the size category <150 g and a rate of 30.1% if fingerling above 300 g weight were stocked.…”
Section: Locusmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we supposed that of the key native pelagic species, the bleak, the common bream and the razor fish are less effected by anthropogenic pressures, and thus, could have a density close to the range of the assumed reference status. On the other hand, population of pikeperch likely is depressed by intensive angling (Specziár and Turcsányi, 2017). On the contrary, as discussed above, both the species richness and the abundance of the phytophilous group could have been much higher in the undisturbed status of Lake Balaton.…”
Section: Reference Statusmentioning
confidence: 93%
“…In this study, pikeperch Sander lucioperca (L. 1758) was used as a model species. Sander lucioperca is a commercially valuable and a game fish, native to eastern Europe and western Asia and introduced to other European, Asian and north African countries (Specziár and Turcsányi, 2017;FAO, 2018). In natural water bodies, S. lucioperca is a top-predator and therefore it is used in many biomanipulative projects to reduce zooplanktivorous species and increase water quality (Wysujack et al, 2002;Blabolil et al, 2016).…”
Section: Introductionmentioning
confidence: 99%